Susi Pudjiastuti’s Language Styles in Her Speech Menjaga Kekayaan Laut Indonesia - Michael; Henny Putri Saking Wijaya (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study analyzes the language styles used by Susi Pudjiastuti in her speech Menjaga Kekayaan Laut Indonesia and the social factors influencing the language styles. The writers used Keraf’s theory of language style (2009) to examine the word choice and sentence structure, and Holmes’ theory of social factors (2013). Employing a qualitative method, the study focused on the utterances containing language styles. The findings show that the most frequently used language style based on word choice was the conversational style. In terms of sentence structure, repetition and climax were the mostly used by Susi Pudjiastuti. These results suggest that social factors namely participant, topic, setting, and function played a role in shaping her language styles. Future research is encouraged to apply the full framework of Keraf (2009) to explore other forms of public communication.